Photon- and Charge-Management in Advanced Energy Materials: Combining 0D, 1D, and 2D Nanocarbons as well as Bulk Semiconductors with Organic Chromophores - Cadranel, Alejandro; Haines, Philipp; Kaur, Ramandeep; Menon, Arjun; Münich, Peter Wilhelm; Schol, Peter; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
In this contribution, seminal works in the area of photon- and charge-management are highlighted with focus on covalent electron donor-acceptor conjugates built around porphyrins (Ps), on one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates are managed by Ps, while 0D, 1D, and 2D nanocarbons serve as the active component, which enable managing charges. With a few leading examples, it can be explored much beyond the simple photon- and charge-management characterization and emphasize photovoltaics and photocatalysis to convert and store energy. This contribution concludes by highlighting recent progress in mixing and matching the unique charge-management features of nanocarbons in the design of multidimensional nanocarbons.
CRIS-Team Scopus Importer:2020-12-11
Keywords: charge management; nanocarbons; photon management; solar-energy conversion